Homeric morality - Yamagata, Naoko. (Mnemosyne, Supplements, 1994)
Homeric Morality is an attempt to answer two questions: whether or not the Homeric gods are concerned with 'justice' in human society, and what mechanism controls the social behaviour of Homeric man. It shows that the gods distribute good and bad fortune to men not in response to their moral behaviour, bus as required by fate; men, however, believe that the gods are concerned with human morality, and subsequently their behaviour is restrained by their faith in the moral gods as well as by many other forces, social and emotional. This volume, taken as a whole, serves as a sustained critique of two influential works in the field, The Justice of Zeus by H. Lloyd- Jones and Merit and Responsibility by A.W.H. Adkins.